Preoperative Mental Health is not Predictive of Patient-reported Outcomes Following a Minimally Invasive Lumbar Discectomy. Issue 10 (December 2017) - Mayo, Benjamin C.; Massel, Dustin H.; Bohl, Daniel D.; Long, William W.; Modi, Krishna D.; Narain, Ankur S.; Hijji, Fady Y.; Lopez, Gregory; Singh, Kern
Abstract : Study Design: This is a retrospective cohort study. Objective: To determine if preoperative mental health is associated with patient-reported outcomes (PROs) following a minimally invasive lumbar discectomy. Summary of Background Data: PROs are commonly used to quantify a patient's perceived health status. Recently, mental health has been theorized to directly affect patients' perception of their disability and pain after spine surgery. Materials and Methods: A registry of patients who underwent a primary, single-level minimally invasive lumbar discectomy was reviewed. The association between preoperative Short-Form Health Survey mental composite score (MCS) and change in PROs [Oswestry Disability Index, back and leg visual analog scale (VAS) pain scores] from preoperative to postoperative (6-week, 12-week, 6-month) timepoints was assessed using multivariate regression controlling for patient demographics and the respective preoperative PRO. Patients in the top and bottom quartiles of preoperative MCS were compared regarding achievement of minimum clinically important difference for each PRO. Results: A total of 110 patients were included in the analysis. Better preoperative mental health was associated with lower preoperative disability and decreased preoperative back VAS ( P <0.05 for each). Higher preoperative MCS was also associated with greater improvements in back VAS at 6-weeks postoperatively ( P <0.05). There was no association between preoperative MCS and change in any PROs at the 12-week or 6-month postoperative visits. Patients in the bottom quartile of preoperative MCS achieved minimum clinically important difference in all PROs at similar rates to patients in the top quartile of preoperative MCS. Conclusions: Patients with better preoperative mental health scores are more likely to report decreased disability and pain preoperatively. However, preoperative mental health was not predictive of changes in long-term disability or pain. As a result, patients with a wide range of preoperative mental health scores can achieve satisfactory long-term reductions in disability and pain levels after a lumbar discectomy. Level of Evidence: Level IV.